PROSPECTS FOR THE DEVELOPMENT OF MEMORIAL-ETHNIC TOURISM IN UKRAINE - Зеленко, Олена; Заваріка, Галина; Юр’єва, Олександра; Булкіна, Людмила (SWorldJournal, 2024)
The article considers the prospects for the development of memorial and ethnic tourism in Ukraine. The purpose of the study is to identify the essence of memorial tourism in the context of the implementation of its ethnic variety; a modern interpretation